Sistem Ekonomi Sunda Dan Ketahanan Pangan Komunal: Model Leuit Kasepuhan Ciptagelar Sebagai Alternatif Tata Kelola Ekonomi Politik Global - Shylvia Windary; Ade Priangani; Fadhilah Yazid Rakasyi; Faza Fadhillah Razaqa (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
Food crises, supply-chain disruptions, climate change, and unequal access to resources reveal the limits of economic governance that relies excessively on market mechanisms and external supplies. This article examines the food economy of the Kasepuhan Ciptagelar community, particularly the leuit granary system and Leuit Si Jimat, as a community-based governance model relevant to global political economy. The study applies a qualitative document-analysis approach using a research report, scholarly articles, books, and institutional publications. Data were analysed through reduction, thematic categorisation, display, and conclusion drawing. The findings identify four dimensions. First, Ciptagelar’s food economy is embedded in customary norms, social relations, and ecological obligations, preventing full commodification. Second, leuit functions as social infrastructure for reserves, risk sharing, and intergenerational continuity. Third, customary leadership, mutual cooperation, adherence to agricultural cycles, and restrictions on rice sales reinforce community food sovereignty. Fourth, market pressures, environmental change, commercialisation, and weak legal protection threaten continuity. Ciptagelar should not be mechanically replicated as a universal model. Nevertheless, its institutional principles, including economic embeddedness, collective governance, decentralised reserves, and cultural legitimacy, can enrich food-security policy. The article contributes by connecting Sundanese local knowledge with embeddedness, common-pool resource governance, food sovereignty, and the pluralisation of global political-economic governance.